Utilization of the fruit meal from the breadfruit tree (Artocarpus altilis) in diets for pre-fattening pigs - Brea, Odel?n; Ortiz, Abel; El?as, Arabel (Cuban Journal of Agricultural Science, 2013)
Fruits from the breadfruit tree (Artocarpus altilis) were collected in the municipality of Yateras, Guant?namo province, Cuba for determining their chemical composition and inclusion levels in diets for pre-fattening pigs. Forty eight recently weaned pigs of the Yorkland x Duroc hybrid of 33 d of age and an average live weight of 9.4 kg were used, according to a completely randomized design with four treatments and three replications. It was confirmed that the fruit meal from the breadfruit tree (BFM) has energy, protein, NDF and ADF qualities that instigates its inclusion in pig diets in the pre-fattening stage. Therefore, it was added at dosages of 0, 10, 15 and 20 % as maize substitute according to the design selected. At the end of the experiment equal viability values (100 %) were obtained in all treatments, while that including 20 % of fruit meal from the breadfruit tree differed significantly regarding the control, attaining lower final live weight and average daily gain. Also, a worsening in DM and CP feed conversions (1.77 to 2.11 kg DM/LW, respectively) was found at P ? 0.05. On decreasing the level of conventional concentrate (0 %) with the inclusion of increasing levels of BFM in the diets, concentrates saving was attained. It is recommended the inclusion, as maximum limit, of 15 % of fruit meal from the breadfruit tree in the diets for pre-fattening pigs without affecting feed and protein conversion regarding the control. Key words: breadfruit tree fruits, pre-fattening pigs